Industrial Maturity: Bridging Capability Development and Business Transformation - Abdullah A Afifi (Journal of Regional Development and Technology Initiatives, 2025)
In today's economic development, business transformation is a key characteristic of the process, as a result of the speed of technological change, digitalization, and the increasing globalisation of production systems. The manufacturing sector is under growing pressure to embrace new technological paradigms like advanced automation, data-driven production, and interconnected ecosystems. In this changing context, the term 'industrial maturity' has become important as a tool to analyse the development of industries from simple production systems to more complex, resilient and innovative systems. The concept of industrial maturity is still not well developed in the academic literature, especially in the explanation of the relationship between capability development and business transformation, despite its increased significance. This study revisits and conceptualizes industrial maturity by combining the concepts of capability theory, the resource-based view, and the literature on business model innovation to understand how technological resources and organizational capabilities can be the drivers of industrial transformation. The paper suggests a conceptual framework that presents industrial maturity as an evolutionary outcome of a combination of technology-driven resources, capability development, and business transformation. Technology-driven resources resemble the technological components of infrastructures, human resources, knowledge assets, and organization that facilitate industrial development. Capability accumulation is the ability of firms to implement, adapt, and deploy these resources effectively. Business transformation is the strategic reconfiguration of capabilities, assets, and business models in response to technological change. The proposed framework emphasizes that industrial maturity is not just a matter of technological adoption but a gradual evolution process that requires technological resource building, strategic adaptation, and ecosystem integration. More mature industries have more advanced technological capacities, adaptive business systems, and more robust innovation networks. This study brings a conceptual approach to the literature on industrial development and lays the groundwork for future empirical studies on business transformation in the digital economy.